Strategies to Optimize the Nutritional Profile of Mammalian Meat for Infants and Geriatric Population - Yoo, Michelle Ji Yeon (Springer Science and Business Media LLC, 2026)
Early-life growth and aging represent physiological stages with increased protein requirements due to rapid tissue development, anabolic resistance and reduced ability to digest and absorb nutrients. Red meat, which includes beef, pork, lamb and goat, provides complete proteins containing all essential amino acids, and micronutrients including iron, zinc, phosphorus, selenium, B vitamins and bioactive molecules such as creatine, taurine and carnitine. This review evaluates the nutritional composition and digestibility of different meat types and meat cuts, and how processing technology may improve protein intake in infants and geriatric population. The vulnerable population require softer texture of meat to ease mastication, swallowing and digestion. Meat cuts have different amino acid profile compared to one another. With the use of moderate temperature thermal processing, high pressure processing, dry ageing/in-bag dry ageing and/or fruit enzymes, protein unfolding, denaturation and proteolysis take place. Dependent on the processing conditions, proteins may become more digestible, liberating free amino acids and short peptides of less than 3 kDa that are easily absorbed by the small intestine for their functions. Conditions can be optimized to target for a release of key amino acids that are crucial for muscle protein synthesis (eg. Branched chain amino acids, including leucine, isoleucine and valine), immunity or cognitive function, which are of particular importance to the infants and geriatric population. By taking this approach, nutritional value of a given quantity of meat can be maximized, while supporting a more sustainable approach to feeding the population with limited resources.
Keywords: Dry aging; Free amino acids; Infant nutrition; Meat protein digestibility; Older adults; 30 Agricultural, Veterinary and Food Sciences; 3003 Animal Production; Nutrition; Aging; Dietary Supplements; 1.1 Normal biological development and functioning; 3001 Agricultural biotechnology; 3006 Food sciences; 4004 Chemical engineering